OPTIMALISASI PERENCANAAN SDM GURU UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA: STUDI LITERATUR - Mutia Insani, Hasna; Isdaryanti, Barokah; Sutarto, Joko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the optimization of teacher human resource (HR) planning to support the implementation of the Merdeka Curriculum in Indonesia. The study is motivated by the fact that teacher readiness remains uneven, particularly in differentiated pedagogy, digital literacy, and project-based learning, indicating that HR planning has not been fully aligned with curriculum demands. The purpose of this research is to analyze and synthesize previous studies related to teacher HR planning strategies in the context of the Merdeka Curriculum. This research employs a qualitative approach using a systematic literature review (SLR) design, analyzing scientific articles published between 2022 and 2026 from indexed journals. Data were collected through structured literature searches and analyzed using content analysis techniques to identify key themes, patterns, and research gaps. The findings reveal that effective HR planning significantly influences curriculum implementation success, involving competency mapping, continuous professional development, and institutional support. Both internal factors (teacher competence, motivation, adaptability) and external factors (leadership, policy support, infrastructure, and training access) affect the effectiveness of HR planning. Furthermore, strategies such as continuous training, mentoring, collaborative learning communities, and technology integration have proven effective in improving teacher readiness. The study concludes that optimizing teacher HR planning requires a strategic, systematic, and sustainable approach aligned with curriculum needs. These findings contribute to the development of educational HR management and provide practical implications for policymakers and school leaders in improving curriculum implementation.